Implication of Physiological and Biochemical Variables of Prognostic Importance in Lead Exposed Subjects - Malik, Arif; Ashraf, Muhammad Abdul Basit; Khan, Muhammad Waqas; Zahid, Ayesha; Shafique, Hassan; Waquar, Sulayman; Gan, Siew Hua; Ashraf, Muhammad (Archives of environmental contamination and toxicology, 2020)
The use of leaded gasoline adversely affects cardiovascular, nervous, and immune systems. Study projects to rule out different variables of prognostic importance in lead-exposed subjects. A total of 317 traffic wardens with 5 years of outdoor experience and Hb levels < 10 µg/dl, and 100 traffic wardens with indoor duties were substituted in two groups. Levels of vitamins, cytokines, lead, iron, minerals, oxidative stress, and lipid peroxidation were estimated with help of their standard ELISA and spectrophotometric methods respectively. The present study show increased levels of lead in subjects (29.8 ± 3.8 vs. 1.5 ± 0.2 µg/dl) that may be involved in increasing oxidative stress, i.e., levels of malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), and isoprostanes were increased in subjects (4.6 ± 0.5, 4.3 ± 0.6 and 37.2 ± 5.1). Moreover, levels of antioxidants, i.e., superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT), were decreased. It also exhibits reduced levels of different enzymes in anemic traffic wardens. Current study concludes that wardens exposed to environmental lead are more susceptible to develop cardiovascular and neurological disorders. It shows that toxicity of lead maybe responsible for redox imbalance and production of proinflammatory cytokines. Thus, early detection of these biomarkers may help to reduce lead toxicity and it also may help to control the dilemma of uncontrolled environmental pollution by implicating strict actions against substandard gasoline.